Epidemiology and Control of Peste des Petits Ruminants (ECO-PPR) toolbox - CGIAR Research Program on Livestock (2019)
The tool has been developed through an interdisciplinary team involving disease experts, epidemiologists, social scientists and economists and has been tested in East and West Africa.